Real-life LDL-C treatment goals achievement in patients with heterozygous familial hypercholesterolemia in the Czech Republic and Slovakia: Results of the PLANET registry - Vrablik, Michal; Raslová, Katarina; Vohnout, Branislav; Blaha, Vladimir; Satny, Martin; Kyselak, Ondrej; Vaclova, Martina; Urbanek, Robin; Maskova, Jana; Soska, Vladimir; Freiberger, Tomas (Atherosclerosis, 2018)
BACKGROUND AND AIMS: Despite the high prevalence of familial hypercholesterolemia (FH) and available effective lipid-lowering therapy, most of the individuals with this disorder remain undiagnosed and undertreated. The aim of the PLANET registry was to assess the real-life attainment of low-density lipoprotein cholesterol (LDL-C) therapeutic target level in patients with heterozygous FH, to characterize prescribed lipid-lowering therapy with assessment of its efficiency according to the attainment of the target LDL-C level, and to characterize cardiovascular events observed in this patient population again in relation to LDL-C target level attainment. METHODS: PLANET registry was designed as a non-interventional, retrospective, cross-sectional, multicentre disease registry for adult patients with heterozygous FH in the Czech Republic and Slovakia. RESULTS: Overall, 1755 patients were enrolled at 32 sites specialized in FH treatment. 15.4% of patients attained the target LDL-C value. The proportion of patients with LDL-C goal achievement increased to 17.3% in the subgroup of patients receiving high-intensity statin therapy (54.6% of study population). Out of 55 patients receiving inhibitors of proprotein convertase subtilisin/kexin type 9 (PCSK9), 61.8% reached the LDL-C treatment goal. Of all cardiovascular events reported, 14.0% occurred in patients attaining the LDL-C goal, while it was 86.0% in the not-at-target group. It was documented (p=0.004) that the longer is the patient in care at the specialized FH centre, the higher is the probability that he/she will attain the target LDL-C level. CONCLUSIONS: Although target LDL-C level attainment remains relatively low, the likelihood of LDL-C goal attainment increases with duration of specialized care.
Keywords: výsledek terapie; inhibitory serinových proteinas; down regulace; Ezetimibe; Cross-Sectional Studies; heterozygot; hodnocení rizik; fenotyp; Male; Cholesterol, LDL; biologické markery; mutace; retrospektivní studie; Genetic Predisposition to Disease; PCSK9 inhibitory; Slovenská republika; proproteinkonvertasa subtilisin/kexin typu 9; Heterozygote; Phenotype; Risk Assessment; Biomarkers; LDL-cholesterol; Serine Proteinase Inhibitors; Česká republika; kombinovaná farmakoterapie; Hydroxymethylglutaryl-CoA Reductase Inhibitors; hyperlipoproteinemie typ II; statiny; Genetic Markers; Slovakia; mužské pohlaví; registrace; Drug Therapy, Combination; genetické markery; Treatment pattern; Czech Republic; Time Factors; Treatment Outcome; Statins; kardiovaskulární nemoci; Down-Regulation; lidé; ženské pohlaví; Proprotein Convertase 9; Humans; anticholesteremika; LDL-Cholesterol; časové faktory; průřezové studie; LDL-C goal attainment; Anticholesteremic Agents; Familial hypercholesterolemia; ezetimib; Cardiovascular Diseases; Mutation; Hyperlipoproteinemia Type II; Registries; Retrospective Studies; Female; PCSK9 Inhibitors; lidé středního věku; genetická predispozice k nemoci; Middle Aged